2013
DOI: 10.1038/jp.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset neutropenia: defining limits of neutrophil count in very low birth weight infants

Abstract: A neutrophil count <1500 μl(-1) after the third week of life is frequently observed in VLBW infants and should not be used as a lower reference limit. The fifth percentile varies according to postnatal age from around 1300 μl(-1) in week 4 of life, decreasing to a nadir of 500 μl(-1) between 3 and 4 months of age. Values normalize in the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Thus, there was no significant relationship between the gender of newborns and neutropenia (p-value=0.4). Vetter-Laracy et al conducted a study on this issue and found that the percentages of male and female newborns in regard to neutropenia were 55% and 45%, respectively [11]. In general, the percentage of male newborns was higher than that of female newborns.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, there was no significant relationship between the gender of newborns and neutropenia (p-value=0.4). Vetter-Laracy et al conducted a study on this issue and found that the percentages of male and female newborns in regard to neutropenia were 55% and 45%, respectively [11]. In general, the percentage of male newborns was higher than that of female newborns.…”
Section: Discussionmentioning
confidence: 97%
“…The low incidence of gram-negative infections in our cohort might explain why a lower threshold yielded similar results. Moreover, as a late-onset physiologic neutropenia frequently occurs in VLBW infants, their I/T ratio might be less accurate [ 23 ]. Consequently, using a lower positivity threshold may be appropriate in order to increase its sensitivity as a screening tool in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Transient neutropenia of infants is typically observed at ~3-4 weeks of life in former preterm newborns who suffered from anemia of prematurity. [138][139][140] It is probably related to HSC competition between compensatory erythropoiesis and granulocytopoiesis. [138][139][140] Severe CN Severe CN syndromes can obviously have their clinical presentation in neonatal age.…”
Section: Transient Of Infantsmentioning
confidence: 99%
“…138–140 It is probably related to HSC competition between compensatory erythropoiesis and granulocytopoiesis. 138–140…”
Section: Special Situationsmentioning
confidence: 99%